2001
DOI: 10.1002/gea.1005
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy, sedimentology, and site formation at Konispol Cave, Southwest Albania

Abstract: Recent geoarchaeological investigations at Konispol Cave (Epirus), Albania concluded nearly a decade of interdisciplinary human ecological investigations. Questions of site formation, cave history, and environmental change were examined through microstratigraphic study and sedimentological analysis. Artifacts and occupation layers from Upper Paleolithic through Iron Age times were preserved in three discrete sediment complexes. Sedimentology supplemented by micromorphology isolated the principal characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…The most common applications of chemical analysis focus on: (a) pre-excavation prospecting to locate and delimit archaeological sites; (b) identifying areas of concentrated activity for full-scale excavation; and (c) delineation of features and activity areas (Cook and Heizer, 1965;Lippi, 1988;Manzanilla and Barba, 1990;Schuldenrein, 1995;Sánchez and Cañabate, 1999;Wells et al, 2000;Parnell et al, 2001). Recently, researchers have successfully expanded this research to study not just open-air sites, but caves and rockshelters as well (Schiegl et al, 1996;Farrand, 2000;Karkansas et al, 2000;Schuldenrein, 2001;Braillard et al, 2004).…”
Section: Chemical Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…The most common applications of chemical analysis focus on: (a) pre-excavation prospecting to locate and delimit archaeological sites; (b) identifying areas of concentrated activity for full-scale excavation; and (c) delineation of features and activity areas (Cook and Heizer, 1965;Lippi, 1988;Manzanilla and Barba, 1990;Schuldenrein, 1995;Sánchez and Cañabate, 1999;Wells et al, 2000;Parnell et al, 2001). Recently, researchers have successfully expanded this research to study not just open-air sites, but caves and rockshelters as well (Schiegl et al, 1996;Farrand, 2000;Karkansas et al, 2000;Schuldenrein, 2001;Braillard et al, 2004).…”
Section: Chemical Analysismentioning
confidence: 98%
“…It has helped archaeologists to understand the construction of earthworks, house floors, and stables (Gebhardt, 1992;Matthews, 1995;Macphail and Goldberg, 1995;Gebhardt and Lanhogr, 1999;Macphail et al, 2003); identify and interpret the nature of agricultural soils and the impact of farming and deforestation on them (Macphail et al, 1987;Courty et al, 1989;Gebhardt, 1992;French and Whitelaw, 1999); and determine the depositional histories of complex archaeological sites, such as caves and rockshelters (Goldberg 1979a(Goldberg , 1979b(Goldberg , 2000Goldberg and Bar-Yosef, 1998;Goldberg and Arpin, 2000;Schuldenrein, 2001;Sherwood, 2001). Micromorphological studies have also allowed for a more refined analysis of burned deposits, including their form, function, and diagenesis (Courty et al, 1989;Schiegl et al, 1996 ;Goldberg and Bar-Yosef, 1998;Karkansas et al, 2000;Sherwood, 2001;Homsey, 2004).…”
Section: Micromorphologymentioning
confidence: 98%
See 1 more Smart Citation
“…Reworked loess and terra rossa may be introduced into rockshelters by this process (see Bar-Yosef, 1993). This mechanism has been recognised in numerous rockshelter and cave sites in the Mediterranean region including Franchthi (Farrand, 1988), Megalakkos (Woodward, 1997b), Konispol (Schuldenrein, 2001), and Aetokremnos (Mandel and Simmons, 1997).…”
Section: Micromorphology and The Source Of The Fine Sediment Fractionmentioning
confidence: 87%
“…The new insights provided by a micromorphological approach revealed that the previous interpretation of these features as paleosols was no longer sustainable. Many of the rockshelters and caves of the Mediterranean region contain reddened sediments that often represent reworked soil materials derived from terra rossa that have been washed, slumped, or blown from their place of origin (Table III; see Bar-Yosef, 1993;Schuldenrein, 2001;Ellwood et al, this issue). Strongly weathered and decalcified soils that are rich in iron oxides with distinctive red hues are a characteristic feature of Mediterranean limestone terrains (Macleod, 1980;Woodward et al, 1994).…”
Section: Micromorphology and The Source Of The Fine Sediment Fractionmentioning
confidence: 99%